Mobile nutrition and health management platform for perioperative recovery: an interdisciplinary research achievement using WeChat Applet - Wu, YuJia; Wang, Xin; Gao, Feng; Liao, JinRong; Zeng, Jie; Fan, Lin (Frontiers in Medicine, 2023)
Background: In recent years, the number of people using mobile applications to promote health and welfare has exponentially increased. However, there are fewer applications in the field of ERAS. How to promote the rapid rehabilitation of patients with malignant tumor surgery during Perioperative period and the mastery of its long -term nutritional state is a problem to be solved. Objective: The purpose of this study is to design and develop a mobile application, and use Internet technology to better manage nutritional health to achieve rapid recovery of patients with malignant tumor surgery. Methods: This study is divided into three stages: 1) Design: Use participating design to make the MHEALTH APP adapt to the clinical practice of nutritional health management; 2) Development: The WeChat Applet of Nutrition and Health Assessment (WANHA) developed using the Internet technology development, and web management programs. 3) Procedure test: patients and medical staff evaluate WANHA's quality (UMARS), availability (SUS) and satisfaction, and conduct semi -structured interviews. Results: In this study, 192 patients with malignant tumor surgery , 20 medical staff used WANHA. Patients with nutritional risks are supported by supporting treatment. The results show that patients who have not been treated during the perioperative period, the incidence of postoperative complications (22.4%) and the average hospitalization time after surgery decreased significantly. The incidence of nutritional risks is nearly more than the preoperative level. 45 patients and 20 medical staff participated in the survey of WANHA's SUS, UMARS and satisfaction. In the interview, most patients and medical personnel believe that the procedure can improve the current medical services and nutritional health knowledge levels, promote the communication of medical staff and patients, and strengthen the nutritional health management of patients with malignant tumors under the concept of ERAS. Conclusions: WANHA is a MHEALTH APP that enhances the nutrition and health management of patients with perioperative period. It can play a huge role in improving medical services, increasing patient satisfaction, and ERAS.